2005
DOI: 10.1111/j.1742-7843.2005.pto_13.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ribose Cysteine Pretreatment on Hepatic and Renal Acetaminophen Metabolite Formation and Glutathione Depletion

Abstract: Ribose cysteine (2(R,S)-D-ribo-(1ø,2ø,3ø,4ø-tetrahydroxybutyl)thiazolidine-4(R)-carboxylic acid) protects against acetaminophen-induced hepatic and renal toxicity. The mechanism for this protection is not known, but may involve inactivation of the toxic electrophile via enhancement of glutathione (GSH) biosynthesis. Therefore, the goal of this study was to determine if GSH biosynthesis was required for the ribose cysteine protection. Male CD-1 mice were injected with either acetaminophen or acetaminophen and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…[ 2 ] Various mechanisms were proved to participate in NAPQI‐induced hepatotoxicity. [ 3 ] Numerous studies have indicated that NAPQI attributes to release of excessive reactive oxygen species (ROS). Moreover, ROS leads to enhanced lipid peroxidation and oxidative stress that have been confirmed to participate in APAP‐induced acute hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Various mechanisms were proved to participate in NAPQI‐induced hepatotoxicity. [ 3 ] Numerous studies have indicated that NAPQI attributes to release of excessive reactive oxygen species (ROS). Moreover, ROS leads to enhanced lipid peroxidation and oxidative stress that have been confirmed to participate in APAP‐induced acute hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Ribose-cysteine is a registered therapeutic goods approved dietary supplement which gives a slower more controlled release of L-cysteine than NAC reducing the potential for toxicity [19]. However, studies on ribose-cysteine are limited and its affect mainly only studied in acute oxidative stress conditions in rodents where it has been shown to increase GSH levels in multiple tissues without toxicity [34,35]. Only one study has investigated the longer term effect of ribose-cysteine showing that daily supplementation (4 mg/day) in the Lp(a) mouse model of hyperlipidaemia for 8 weeks promotes a significant increase in GSH and GPx in the liver and blood, without toxicity [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, when taken in excess, it produces severe hepatotoxicity, which is often fatal . Under normal conditions, acetaminophen is metabolically activated by cytochrome P450 2E1 to form a reactive metabolite, N ‐acetyl‐ p ‐benzoquinone imine (NAPQI) . At therapeutic doses, NAPQI is efficiently detoxified, principally by conjugation with glutathione (GSH) under glutathione S ‐transferase (GST)‐mediated conditions to the 3‐glutathione‐ S ‐yl‐acetaminophen conjugate that excreted by the kidney .…”
Section: Introductionmentioning
confidence: 99%